„Przynależność do narodu kompletnie pozbawionego znaczenia”. Soren Gauger jako polski pisarz z Kanady - Piotr Marecki (Postscriptum Polonistyczne)
Soren Gauger is a Canadian writer who has decided to write in Polish. The author of the article examines the writer’s motivations, the way he develops his ideas and his first literary creation in Polish. Soren Gauger’s works reflect his attitude towards Polish culture where he invents defence mechanisms based on feelings of inferiority. In Soren Gauger’s literary works he can be seen to be disregarding the influence of popular trends in hegemonic cultures, referring to old and oldfashioned works, and styling himself on marginality and fantasticality.